Analisis Pengaruh Kualitas Layanan dan Promosi Terhadap Keputusan Peminjaman Nasabah dan Dampaknya Terhadap Kepuasan Nasabah : Studi Pada PT. Bank Rakyat Indonesia, Tbk Unit Peta Utara - Muhammad Rusydi Hawari; Djumarno (Warta Pendidikan | e-Journal, 2020)
This study aims to discuss the effect of service quality and promotion on customer lending decisions that have impact on customer satisfaction. The object of the study was the customer of Bank BRI in peta utara unit, which had already loans KUR and had completed the KUR loan requirements. The independent variable obtained from the pre-survey results to 35 respondents is the service quality and promotion variable, there are also dependent variables namely the loan decision variable and the customer satisfaction variable. This research uses the SEM (Structural Equation Model) data analysis method which data processing uses LISREL analysis. The total population of this study was 195 respondents. The results of the research data were tested using LISREL software version 8.80, it was found that service quality perception had a positive and significant effect directly on customer lending decisions as evidenced by the t-value 5.99, greater than 1.96, and the estimated value of 0.45 or 45.0%, promotion positive and significant effect directly on customer lending decisions as evidenced by t-value 6.71 greater than 1.96, and estimated value of 0.52 or 52.0%, service quality has a positive and significant effect directly on customer satisfaction evidenced by t-value 5.48 is greater than 1.96, and the estimated value is 0.47 or 47.0%, promotion has a positive and significant direct effect on customer satisfaction as evidenced by a t-value 3.61 greater than 1.96, and the estimated value amounting to 0.31 or 31.0% and customer lending decisions have a positive and significant direct effect on customer satisfaction as evidenced by t -value 2.24 is greater than 1.96, and the estimated value is 0.23 or 23.0%.